Perspektif pengguna pada penyebaran informasi kesehatan mental melalui akun Instagram @ibunda.id - Shalsa Dwi Azzahra; Agus Rusmana (Faculty of Communication, Padjadjaran University, 2023)
Everyone needs information to support his varied activities. The development of technology and communication has produced social media, such as Instagram which can be used as a medium for disseminating information. The dissemination of information on Instagram aims to become a forum for its users to participate, share and exchange all information such as, mental health issues that currently become the concern of many people. Mental health is a sensitive issue, especially after the Covid pandemic. Mental health is an important dimension of life and becomes a supporting aspect for humans to carry out social activities in their environment. This study aims to determine users' perspectives on mental health information dissemination through Instagram @ibunda.id. This research uses Cognitive Response Theory and qualitative research with a case study approach. The data was collected from interviews, literature, and documentation. Sampling in this study was determined by purposive sampling technique. Data were analyzed through a series of data collection processes, description, reduction, and conclusion. The results show that @ibunda.id is proven to be able to meet the mental health information needs of its followers. Through this, followers tend to apply behaviours of caring for mental health in their life. This research shows that using the Instagram application for information dissemination is appropriate and effective because it's a modern and user-friendly educational platform.